ACTIVITIES TO ANTICIPATE THE WEAKNESSES OF STUDENTS’ READING MATERIALS FROM INTERNET - Mulatsih, Maria Eka (Lire Journal (Journal of Linguistics and Literature), 2020)
The shift of the way of reading from printed material into non-printed material (reading from the computer, tablet, and smartphone) happened in the past few years ago. This shift affects students’ learning and reading processes inside or outside the class. Previous researches have shown the negative impact of reading on screen. This article explores students’ reading materials from the internet today in relation to its’ weaknesses when an adaptation of the Extensive Reading procedure was applied in Prose and Book Report classes of English Language and Education Study Program during even semester 2018. Students were free to choose their reading materials which consisted of two short stories and four novels for Prose class, three simplified novels and three original novels for Book Report class. Not surprisingly, most students showed their interest in reading some literary works taken from some internet sources. Knowing the weaknesses of the source is needed so the teachers or lecturers can anticipate the problem that can be caused by reading those materials. It was found that students’ reading material from a certain internet source did not have a good structure of English due to some causes. Further activities for students who chose that source could be done so that students knew the weaknesses and tried to overcome them.